Lateral Diffusion of Peripheral Membrane Proteins on Supported Lipid Bilayers Is Controlled by the Additive Frictional Drags of 1) Bound Lipids and 2) Protein Domains Penetrating into the Bilayer Hydrocarbon Core - Ziemba, Brian P. (2013)
Peripheral membrane proteins bound to lipids on bilayer surfaces play central roles in a wide array of cellular processes, including many signaling pathways. These proteins diffuse in the plane of the bilayer and often undergo complex reactions involving the binding of regulatory and substrate lipids and proteins they encounter during their 2-D diffusion. Some peripheral proteins, for example pleckstrin homology (PH) domains, dock to the bilayer in a relatively shallow position with little penetration into the bilayer. Other peripheral proteins exhibit more complex bilayer contacts, for example classical protein kinase C isoforms (PKCs) bind as many as six lipids in stepwise fashion, resulting in the penetration of three PKC domains (C1A, C1B, C2) into the bilayer headgroup and hydrocarbon regions. A molecular understanding of the molecular features that control the diffusion speeds of proteins bound to supported bilayers would enable key molecular information to be extracted from experimental diffusion constants, revealing protein-lipid and protein-bilayer interactions difficult to study by other methods. The present study investigates a range of 11 different peripheral protein constructs comprised by 1 to 3 distinct domains (PH, C1A, C1B, C2, anti-lipid antibody). By combining these constructs with various combinations of target lipids, the study measures 2-D diffusion constants on supported bilayers for 17 different protein-lipid complexes. The resulting experimental diffusion constants, together with the known membrane interaction parameters of each complex, are used to analyze the molecular features correlated with diffusional slowing and bilayer friction. The findings show that both 1) individual bound lipids and 2) individual protein domains that penetrate into the hydrocarbon core make additive contributions to the friction against the bilayer, thereby defining the 2-D diffusion constant. An empirical formula is developed that accurately estimates the diffusion constant and bilayer friction of a peripheral protein in terms of its number of bound lipids and its geometry of penetration into the bilayer hydrocarbon core, yielding an excellent global best fit (R(2) of 0.97) to the experimental diffusion constants. Finally, the observed additivity of the frictional contributions suggests that further development of current theory describing bilayer dynamics may be needed. The present findings provide constraints that will be useful in such theory development.